Impact of Skipping Breakfast on Adolescent Health: A Review - Luiz Antonio Del Ciampo; Ieda Regina Lopes Del Ciampo (Archives of Current Research International, 2025)
Breakfast is considered to be the most important meal of the day, usually eaten within 2 hours of waking up and before starting daily activities. As it is the first meal after a physiological break with consciousness during the night, breakfast takes on great importance due to the time at which it is consumed and its nutritional components. Not eating breakfast has become a universal problem almost inherent to modern life, with prevalence can vary from 10% to 48% among adolescents, and is higher among girls. Adolescents are a group with many specific nutritional, emotional and social demands. Due to rapid body transformations, they need energy and nutrients for adequate growth, physical activity and academic performance, which makes them highly vulnerable nutritionally, since alterations or deficiencies occurring at this age can have repercussions on future life. This article is a mini-review covering the most recent studies on the subject and presents the main characteristics related to the role of breakfast and its importance in the daily diet, especially for adolescents, highlighting their nutritional needs, the repercussions that skipping breakfast can have on their health and quality of life and indicating possible measures that can be adopted to reverse this condition.